First MESSENGER orbital observations of Mercury's librations. Issue 19 (3rd October 2015) - Stark, Alexander; Oberst, Jürgen; Preusker, Frank; Peale, Stanton J.; Margot, Jean‐Luc; Phillips, Roger J.; Neumann, Gregory A.; Smith, David E.; Zuber, Maria T.; Solomon, Sean C.
Abstract: We have coregistered laser altimeter profiles from 3 years of MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) orbital observations with stereo digital terrain models to infer the rotation parameters for the planet Mercury. In particular, we provide the first observations of Mercury's librations from orbit. We have also confirmed available estimates for the orientation of the spin axis and the mean rotation rate of the planet. We find a large libration amplitude of 38.9 ± 1.3 arc sec and an obliquity of the spin axis of 2.029 ± 0.085 arc min, results confirming that Mercury possesses a liquid outer core. The mean rotation rate is observed to be (6.13851804 ± 9.4 × 10 −7 )°/d (a spin period of 58.6460768 days ± 0.78 s), significantly higher than the expected resonant rotation rate. As a possible explanation we suggest that Mercury is undergoing long‐period librational motion, related to planetary perturbations of its orbit. Key Points: The libration amplitude, rotation rate, and pole orientation of Mercury have been measured The non‐resonant rotation rate is interpreted in terms of a long‐period libration Implications for Mercury's moment of inertia and interior structure are discussed